Autonomic disorder in systemic lupus erythematosus: autoimmune autonomic ganglionopathy - Naoto Azuma; Mai Nakano; Masao Tamura; Chie Ogita; Kazuhiro Kitajima; Tetsuya Furukawa; Kiyoshi Matsui (Immunological Medicine)
The pathomechanisms of autonomic disorders in systemic lupus erythematosus (SLE) remain unclear. We herein report a patient with SLE who developed autonomic disorders presumably caused by autoimmune autonomic ganglionopathy (AAG). A 42-year-old woman with SLE under treatment with corticosteroids and hydroxychloroquine was admitted for recurrence of SLE with thrombocytopenia and nephritis. On admission, she presented with weight loss, orthostatic dizziness, abdominal distension, and difficulty urinating. Marked intestinal dilatation, kidney swelling, bilateral hydronephrosis, and ureteral dilatation were noted on ultrasonography and computed tomography. No evidence of obstruction was observed in the intestines, urinary tracts, or bladder. Transverse myelitis was also ruled out by magnetic resonance imaging. After starting the treatment for the recurrent SLE (intravenous immunoglobulin and methylprednisolone pulse therapy, followed by high-dose oral corticosteroid, mycophenolate mofetil, and tacrolimus), orthostatic dizziness, abdominal distension, and difficulty urinating subsided along with increases in platelet count and decreases in urinary protein. The intestinal dilatation, hydronephrosis, and ureteral dilatation improved. We inferred that her SLE was complicated by AAG based on a positive anti-ganglionic acetylcholine receptor antibody. This case suggested that AAG should be considered as a type of autonomic disorder in SLE.